27-GAUGE VITRECTOMY WOUND INTEGRITY: A Randomized Pilot Study Comparing Angled Versus Straight Entry in Fluid-Filled Vitrectomized Eyes. Issue 4 (April 2018) - Khan, M. Ali; Durrani, Alia K.; Hsu, Jason; Regillo, Carl D.
Abstract : Purpose: To compare clinical outcomes using angled versus straight trocar insertion during 27-gauge pars plana vitrectomy for epiretinal membrane. Methods: Pilot randomized controlled trial. Thirty eyes of 30 patients undergoing 27-gauge pars plana vitrectomy with membrane peeling for epiretinal membrane were randomized 1:1 to receive angled or straight trocar insertion. Intraocular pressure (IOP) and postoperative wound-related complications were compared. Results: Fifteen eyes were randomized to each the angled and straight incision groups. No significant difference in phakic status ( P = 0.71) or preoperative IOP (15.1 ± 3.4 vs. 14.6 ± 3.0 mmHg, P = 0.67) existed between groups. On postoperative Day 1, eyes in the straight group had lower IOP compared with the angled group (11.8 ± 3.9 vs. 15.3 ± 5.2 mmHg, P = 0.04) and a relative decrease in IOP compared with preoperative values (11.8 ± 3.9 vs. 15.1 ± 3.4 mmHg, P < 0.01). No IOP difference between groups was present at Day 7 ( P = 0.43) or Day 30 ( P = 0.42). Postoperative complications included transient hypotony (1 eye, straight group) and serous choroidal detachment (1 eye, angled group). Conclusion: Eyes with straight incisions had transiently lower IOP on postoperative Day 1, possibly suggestive of subclinical wound leak in the very early postoperative period. Overall, rates of hypotony and sclerotomy-related complications were similarly low between wound construction strategies. Abstract : Both angled and straight trocar insertion was well tolerated during 27-gauge pars plana vitrectomy for epiretinal membrane. Overall, rates of hypotony and sclerotomy-related complications were similarly low between wound construction strategies.